Motor Car & Coach Painting for Private, Commercial and Mass Output - Oliver, Charles E. (Charles Edwin) (W. R. Howell & Co., 1926)
Second edition volume with chapters on the motor car painting process, a special chapter on "Painting with Nitrocellulose Products," and several chapters on motor painting material specifications. The volume includes nine colored plates and a frontispiece with sample paint swatches adhered. Some swatches are damaged or missing. The work is digitized in its entirety. The Holden group originated in a small business established in Birmingham in the 1830s, manufacturing, among other things, varnish for church pews and black enamel for tin trunks. In 1865, the business was acquired by Arthur Holden and focused its production on general industrial finishes, eventually including the "Durus" enamels pictured in this book.
Keywords: Automobiles; Automobiles--Painting; Painting, Industrial; Motor vehicles--Painting; Paint; Nitrocellulose; Arthur Holden & Sons, Ltd.